The LRRK2 Variant E193K Prevents Mitochondrial Fission Upon MPP+ Treatment by Altering LRRK2 Binding to DRP1 - Perez Carrion, Maria; Pischedda, Francesca; Biosa, Alice; Russo, Isabella; Straniero, Letizia; Civiero, Laura; Guida, Marianna; Gloeckner, Christian J.; Ticozzi, Nicola; Tiloca, Cinzia; Mariani, Claudio; Pezzoli, Gianni; et al. (Frontiers in Molecular Neuroscience, 2018)
Mutations in leucine-rich repeat kinase 2 gene (LRRK2) are associated with familial and sporadic Parkinson’s disease. LRRK2 is a complex protein that consists of multiple domains, including 13 putative armadillo-type repeats at the N-terminus. In this study, we analyzed the functional and molecular consequences of a novel variant, E193K, identified in an Italian family. E193K substitution does not influence LRRK2 kinase activity. Instead it affects LRRK2 biochemical properties, such as phosphorylation at Ser935 and affinity for 14-3-3e. Primary fibroblasts obtained from an E193K carrier demonstrated increased cellular toxicity and abnormal mitochondrial fission upon 1-methyl-4-phenylpyridinium treatment. We found that E193K alters LRRK2 binding to DRP1, a crucial mediator of mitochondrial fission. Our data support a role for LRRK2 as a scaffolding protein influencing mitochondrial fission.